Assessment and evaluation efficacy of a clinical pharmacist-led inpatient warfarin knowledge education program and follow-up at a Chinese tertiary referral teaching hospital - Guy-Armel Bounda; Cosette Ngarambe; Wei Hong Ge; Feng Yu (Archives of Pharmacy Practice, 2013)
Background: Oral anticoagulation therapy with warfarin is used to prevent and to treat venous and arterial thrombosis and embolism. Its narrow therapeutic index should be monitored carefully in order to reach the desired outcomes. Objective: This study aims to evaluate the clinical pharmacist-led in-patient warfarin′s knowledge education program and to assess a follow-up efficacy in a Chinese tertiary referral teaching hospital. Design and Setting: A cross-sectional and observational study was conducted at the Affiliated Hospital of Medical College of Nanjing University, a 1460-bed tertiary referral teaching hospital in Nanjing. Materials and Methods: One-on-one interview questionnaire was conducted among 47 Chinese patients who had undergone prosthetic valve replacement. Before the patient education program′s implemented, at discharge time and 3 months, 6-9 months and 12 months after surgery were considered as time points. A previously validated 17-item questionnaire was used to measure the patient′s knowledge level of warfarin and to assess and evaluate a follow-up efficacy of this patient education program run by a clinical pharmacist. Knowledge scores were compared using the Student′s t-test or one-way analysis of variance. Main Outcome Measure: Patients′ knowledge on the warfarin education program and warfarin knowledge score, drug therapy problems or bleeding complication events associated to warfarin therapy and evaluation of clinical pharmacist′s service provided. Results: Patients mean age was 47.68 ΁ 9.70 years (range 23-67). The higher education strata had significantly higher warfarin knowledge scores (P < 0.05). In terms of hospital stay post-surgery, compared with other groups, patients with an average of 11-14 days, were found significantly and statically higher knowledgeable in warfarin (P < 0.05). The clinical pharmacist′ service was found very satisfying f(80.85%). Conclusion: Chinese patients on warfarin therapy should benefit from periodic educational efforts reinforcing key medication safety information. Patient education is not a once-off procedure. A complete patient education program run by a clinical pharmacist in a Cardio-thoracic ward can considerably improve and enhance to reduce the hospital stays and significantly enlighten the role of the patient education in adherence to therapy.